ChemInform Abstract: Palladium‐Catalyzed Regio‐ and Stereoselective Carbothiolation of Terminal Alkynes with Azolyl Sulfides. Issue 32 (22nd July 2016) - Iwasaki, Masayuki; Topolovcan, Nikola; Hu, Hao; Nishimura, Yugo; Gagnot, Glwadys; Na nakorn, Rungsaeng; Yuvacharaskul, Ramida; Nakajima, Kiyohiko; Nishihara, Yasushi
Abstract: A wide range of (azolyl)alkenyl sulfides are prepared with excellent regio‐ and stereoselectivity.